Sensitized Fluorescence Organic Light-Emitting Diodes with Reduced Efficiency Roll-Off - Li, Zhiyi; Wang, Ruifang; Zeng, Yangyang; Dong, Xiangyu; Liu, Guanhao; Hu, Xiaoxiao; Gao, Teng; Gao, Honglei; Qin, Yuanyuan; Gu, Xiuxian; Lee, Chun-Sing; Liu, Jiguang; Wang, Pengfei; Wang, Ying (Organic Materials, 2021)
Thermally activated delayed fluorescence (TADF)-sensitized fluorescence is a promising strategy to maintain the advantage of TADF materials and fluorescent materials. Nevertheless, the delayed lifetime of the TADF sensitizer is still relatively long, which causes heavy efficiency roll-off. Here we reported a valid tactic to construct fluorescent devices with low-efficiency roll-off by utilizing the TADF sensitizer with a reduced delayed lifetime. By the construction of the sensitization system, the energy transfer efficiency can reach up to 90%. The high-energy transfer efficiency and the TADFʼs short delayed lifetime result in high sensitization over 95% and the maximum external quantum efficiency of 16.2%. Meanwhile, the TADF-sensitized fluorescent devices exhibit reduced efficiency roll-off with an “onset” current density of 23 mA · cm−2. Our results provide an effective strategy to reduce the efficiency roll-off of the TADF sensitization system.
Keywords: OLED; fluorescence; TADF